Release of acetylcholine by chick embryo heart before innervation - Coraboeuf, E. (1970)
1. In chick embryo hearts, 3-day-old and not yet innervated, repetitive direct stimulation causes a transitory inhibition of the spontaneous rhythm. 2. The degree of post-stimulation inhibition depends on the frequency and duration of the artificial stimulation and on the concentration of K and Ca ions in the extracellular solution. 3. After treatment with atropine (10(-5) g/ml.) post-stimulation inhibition is no longer observed. The spontaneous rhythm is accelerated by atropine. The findings therefore suggest that an ACh-like substance is released from the non-innervated embryonic heart during activity. 4. By use of the dorsal muscle of the leech for biological assay the liberation of an ACh-like substance from the non-innervated embryonic heart was confirmed.